La sobreprotección familiar y sus efectos en el desarrollo motriz en niños del nivel preparatoria - Tigse Herrera, Carmen Inés (2022)
The present investigation with the title: "Family overprotection and its effects on motor development in children at the kindergarten level" addressed the causes and consequences of overprotection in motor development in first grade children. It is mentioned that overprotection is the excessive desire to prevent children from suffering any harm, being it physical or emotional, no matter how minimal, limiting the possibility of carrying out activities in the environment according to age and that strengthen the acquisition of responsibility and awareness of the actions, the main objective has been set, to develop strategies to strengthen motor development in kindergarten children of the Ernesto Che Guevara Educational Institution; The research methodology has a quantitative approach, since the scientific method has been used, based on an existing theory, working with two variables: family overprotection and motor development, which have a cause-effect relationship; which leads to the systematization of the proposal that consists of the elaboration of a practical guide for the stimulation of motor development in kindergarten children addressed to teachers, in order to provide tutors with a tool that helps to improve and overcome the effects of overprotection on motor development, based on the diagnosis made, the results obtained allowed to identify that there is a correlation between family overprotection and motor development in kindergarten children, who mostly do not have adequate development motor as an effect of family overprotection. After the development and application of the strategies proposed in the proposal, it was possible to show that, with the appropriate strategies where the possibilities of movement are allowed to be known, it is possible to strengthen and enhance the motor development of children.